2005
DOI: 10.1002/ijc.21639
|View full text |Cite
|
Sign up to set email alerts
|

Predominant T helper type 2‐inflammatory responses promote murine colon cancers

Abstract: Colon cancer is one of the most serious complications of inflammatory bowel diseases, especially ulcerative colitis (UC). Previous studies have shown that characteristic immunological event during inflammation in UC is the expression of T helper-type 2 (Th2) cell-derived cytokines. In this study, we investigated the influence of a predominant Th2-type cytokine response in colitis on carcinogen-induced colon tumors. Wild type (WT), interferon gamma (IFN-c) gene deficient (2/2) [Th2 dominant] or interleukin (IL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 36 publications
3
46
1
Order By: Relevance
“…Previously, Th2 response was associated with the tumor immune evasion in mice studies (24,25), or not associated with clinical outcome in human studies (26,27). Our study does not support a major role of Th2 cells on patient's prognosis.…”
Section: Discussioncontrasting
confidence: 78%
“…Previously, Th2 response was associated with the tumor immune evasion in mice studies (24,25), or not associated with clinical outcome in human studies (26,27). Our study does not support a major role of Th2 cells on patient's prognosis.…”
Section: Discussioncontrasting
confidence: 78%
“…In vivo, IFNg expression protects from tumor in different tumor models (31)(32)(33). In a murine model of CAC, Osawa and colleagues showed that IFNg-deficient mice are more susceptible to develop CAC (34). IFNg expression is also essential for CD8-mediated antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…A predominant T helper 2 inflammatory response has been implicated in colon cancer and IFNg deficiency increased the frequency of colonic neoplasms (20). The low levels of IFNg observed in Tir8 À/À colons could be indicative of a T helper 2 polarized environment.…”
Section: Discussionmentioning
confidence: 99%